Recombinant laccase biosynthesis for efficient polydopamine coating - Magalhães, Flávia F.; Neves, Márcia C.; Pedro, Augusto Q.; Freire, Mara G.; Santos-Ebinuma, Valéria C. [UNESP]; Tavares, Ana P.M. (Elsevier, 2024)
Laccases are versatile biocatalysts with interest for various industrial applications. This study reports the expression of Trametes versicolor laccase in Komagataella phaffii X33. The cultivation parameters (methanol and CuSO4 concentration, and temperature) for recombinant laccase production were studied in an orbital shaker. Enhanced laccase production was achieved by adding 1 % (v/v) methanol daily, supplementing 0.1 mM CuSO4 and incubating at 25 °C. Under these conditions, laccase production was scaled-up in a 4 L stirred tank bioreactor. Subsequently, laccase was concentrated and purified using a combined protocol of ultrafiltration and acetone precipitation, achieving a purification factor of 3.02. The laccase produced exhibited robust stability within a pH range from 4.0 to 8.0 and thermal stability up to 30 °C. Michaelis Menten kinetic revealed Michaelis constant (KM) and maximum rate of reaction (Vmax) values of 44.5 µM and 110.9 µM/min, respectively. Finally, laccase was employed as a biocatalyst to assist the polymerization of dopamine to polydopamine, allowing the one-step coating of cellulose filter paper, as confirmed by diffuse reflectance spectroscopy (UV-Vis DRS) and scanning electron microscopy (SEM). This work represents an advance in the field of laccase production in both orbital shaker and bioreactor, while demonstrating, for the first time, the laccase-assisted polymerization of dopamine for the coating of filter paper with polydopamine.
Keywords: Bioproduction; Coating; Komagataella phaffii; Laccase; Polydopamine